Transforming Local Livelihoods to Community Enterprises in Guinayangan, Quezon Province - Tacugue, Maria Christy Jesusa; Tolentino, Francisco; Vidallo, Rene R.; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The transformation of livelihoods to community based enterprises entails time, involves community participation and support from local government units. This paper will describe the processes by which the initial phase of agri fishery enterprise development in the Municipality of Guinayangan was implemented. This project was undertaken in collaboration with the Department of Agriculture Region IV A and, the local government of Guinayangan